Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

first my definition of a coset that I got is: Definition. Let $H$ be a subgroup of a group $G$. A left coset of $H$ in $G$ is a subset of $G$ that is of the form $xH$, where $x\in G$ and $$xH = \{y\in G | y = xh \text{ for some }h\in H\}.$$

And here is the theorem that is confusing me.

Let $H$ be a subgroup of a group $G$. Then the left cosets of $H$ in $G$ have the following properties:

  1. $x\in xH$ for all $x\in G$;
  2. if $x$ and $y$ are elements of $G$, and if $y = xa$ for some $a\in H$, then $xH = yH$;
  3. if $x$ and $y$ are elements of $G$, and if $xH \cap yH$ is non-empty then $xH = yH$.

$\textbf{Proof.}$ Suppose $x\in G$. Then $x = x1$, but $1$ is in $G$ and $H$ since $H$ is a subgroup of $G$. Thus $x\in xH$, which proves (1).

Suppose $x$ and $y$ are elements of $G$ and we can choose some $a\in H$ such that $y = xa$. Now suppose $z\in yH$. It follows that $z = yh$ for some $h\in H$. But $y = xa$, so we know that $z = xah$. Since $H$ is a subgroup and $a\in H$ and $h\in H$ it follows that $ah \in H$, hence $z\in xH$. Since $z$ was an arbitrary element of $yH$ we can conclude that $yH\subseteq xH$. Now suppose $z\in xH$. It follows that $z = xh$ for some $h\in H$. But $x =ya^{-1}$, so $z = ya^{-1}h$. Since $H$ is a subgroup and $a\in H$ it follows that $a^{-1}$ is in $H$. Similarly, since $a^{-1}\in H$ and $h\in H$ it follows that $a^{-1}h \in H$, thus $z\in yH$. Since $z$ was an arbitrary element of $xH$ we can conclude that $xH \subseteq yH$. Therefore we can conclude that $xH = yH$, which proves (2).

Now suppose that $x$ and $y$ are elements of $G$ and $xH \cap yH$ is non-empty. Since $xH \cap yH$ is non-empty we can choose some $z\in xH \cap yH$. Since $z\in xH\cap yH$ it follows that $z\in xH$ and $z\in yH$. Thus $z = xh_x$ with $h_x \in H$ and $z = yh_y$ with $h_y \in H$. Thus, since $z = z$ in all groups, $yh_y = xh_x$. Hence, $y =xh_xh_y^{-1}$. Since $H$ is a subgroup $x\in H$, $h_x\in H$ and $h_y\in H$, we can conclude that $xh_xh_y^{-1} \in H$. Therefore by (2) we know that $xH = yH$, which proves (3). $\Box$

Now my confusion stems from (1) and (3).

Suppose $G = \{x_1, x_2, ..., x_n\}$ under $\star$ Then each element $x_i$ of $\{x_1, x_2, ..., x_n\}$ is a member of $x_iH$ by (1).

By (3) we know that no element $x_i$ can be a member of two sets $x_iH$ and $x_jH$.

But since each $x_iH$ is a subset of $\{x_1, x_2, x_3, ..., x_n\}$, so it would seem to me that each coset would have to contain only one element.

Where am I wrong in my thinking here? Thank you very much

share|cite|improve this question
up vote 1 down vote accepted

An element $x_i$ can be a member of $x_iH$ and $x_jH$ if $x_iH$ and $x_jH$ are simply different names for (or descriptions of) the same set.

Think about the coset $1_GH = H$ for starters: for every $h \in H$, $hH = H$. All of the cosets $hH$ with $h \in H$ are the same coset, namely, $H$ itself. While this is most obvious in the case of $H$, the same thing is true of all other cosets of $H$: if $C$ is any coset of $H$, then $gH = C$ for every $g \in C$.

You might try to prove that for any $x,y \in G$, $xH = yH$ if and only if $x^{-1}y \in H$; all of the ingredients can be found in your proof of (1)-(3).

share|cite|improve this answer
Thanks very clear answer, and thanks for the suggestion I will try proving it later when I can get to my computer – Deven Ware Aug 11 '11 at 0:13
Thanks for editing your response :) – Deven Ware Aug 12 '11 at 17:48

It might be that $x_1H = x_2H$, even though $x_1 \neq x_2$. In particular, if $h$ is in $H$, then $hH = 1H = H$, even though $h$ need not be equal to $1$.

In general, if $H$ has $m$ elements, then $xH$ has $m$ elements too. The cosets divvy up $G$ into pieces of size $m$. Each piece has $m$ different names, $(xh) H = xH$ for all $m$ possible $h$s in $H$.

If $G$ is the group of points in the Cartesian plane (the operation being addition), and $H$ is a line through the origin (for instance the $x$-axis, the $y$-axis, or the line $y=x$ all form subgroups), then the cosets of $H$ are all the parallel lines to $H$. Each line can be named by any of the points on it.

share|cite|improve this answer
Thank you, cleared up my cofusion so simply very much appreciate it :) – Deven Ware Aug 11 '11 at 0:01

(iii) only says that $x_i H$ and $x_j H$ are either the same, or completely disjoint. Thus if you pick any element $y$ from $xH$, then it will necessarily be the case that $xH = yH$. Note that this does not imply that $x=y$, only that $xH = yH$.

For instance consider the group $G = \{1,x,y,xy\}$ where $x^2 = 1$ and $y^2 = 1$ and consider the subgroup $H = \{1,x\}$.

The coset $1 H = \{1, x\}$ and the coset $xH = \{x, x^2\} = \{1,x\}$. Thus $1H = xH$.

The coset $yH = \{y, yx\}$ which is disjoint from $1H$.

share|cite|improve this answer
Thank you very much, I'm no longer confused :) – Deven Ware Aug 11 '11 at 0:02

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.